RANCANGAN BUKU TEKNIS PENYUSUNAN SOAL UJIAN SEKOLAH BERSTANDAR NASIONAL (USBN) MATA PELAJARAN IPA BAGI GURU SMP - Rusela, Izma; Suryawati, Evi; Natalina, Mariani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to produce a quality book for technical question preparation USBN of science subjects for junior high school teachers. The process of developing book is carried out in the University of Riau Biology Education Study Program and a limited trial is conducted in MGMP Pekanbaru. The time of the research was May until December 2018. The development model used was the ADDIE model until the development stage. Research subjects were direction of USBN 2017/2018. The instruments used are validation sheets, student response questionnaires and book product that have been developed. The data were collected by filling the validation sheet by five validators (three lecturers of Biology Education and two natural science teachers), fill out the respondents questionnaire. The validation sheet filled using Likert scale and will be analyzed by calculating the mean of all validators. Average score of book that has been developed that is, include format and grafical aspects is 3,32, illustrations and draw aspects is 3,20, language aspects is 3,28, and content aspects is 3,33. The category of all scores of the five aspect is valid-very valid. The average validation is 3,28 (very valid). The response in first simulation is 3,56 and the response in second simulation is 3,25 which is categorized very good. Based on the result of validation and limited trial, can be conclussion that quality of book is very valid and already to implementation, can be used by teachers as one of the independent learning resources for prepare and arrange the standard question especially USBN, and can be used as a reference by the natural science teachers.Key Words: Book, IPA, SMP, Technical Question Preparation, National Standardized School Examination (USBN)